(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
This work is devoted to the analysis of the capabilities of small units of hydraulic turbines for operation in conditions of the presence of water flows with low flow velocities and low slope angles of the terrain, and also provides information regarding developments on this topic in Europe. The designs and possibilities of new developments for pico - and micro-hydraulic turbines are considered.